Investigation of percentage changes in pulse wave transit time induced by mini‐fluid challenges to predict fluid responsiveness in ventilated dogs. Issue 4 (20th June 2019) - Sano, Hiroki; Fujiyama, Masako; Wightman, Paul; Cave, Nick J.; Gieseg, Mike A.; Johnson, Craig B.; Chambers, Paul
Abstract: Objective: To investigate whether percentage changes in pulse wave transit time (PWTT%Δ) induced by mini‐fluid challenges predict fluid responsiveness in mechanically ventilated anesthetized dogs. Design: Prospective experimental trial. Setting: University teaching hospital. Animals: Twelve Harrier hounds. Intervention: Each dog was anesthetized with propofol and isoflurane after premedication with acepromazine, mechanically ventilated, and had a fluid challenge. This was repeated 4 weeks later. The fluid challenge, 10 mL/kg of colloid administration over 13 minutes, consisted of 3 intermittent mini‐fluid challenges (1 mL/kg of each over a minute) with a minute interval, and the remaining colloid administration (7 mL/kg) over 7 minutes. Measurements and Main Results: Percentage change in velocity time integral of pulmonary arterial flow by echocardiography was calculated as an indication of change in stroke volume. Fluid responsiveness was defined as percentage change in velocity time integral ≥ 15% after 10 mL/kg colloid. Dogs responded on 14 fluid challenges and did not on 10. After 1, 2, 3, and 10 mL/kg of fluid challenge, PWTT%Δ1, 2, 3, 10 were measured. Receiver operator characteristic (ROC) curves were generated and areas under ROC curve were calculated for PWTT%Δ1, 2, 3 . A gray zone approach was used to identify the clinically inconclusive range. The area under the ROC curve for PWTT%Δ3 was 0.91 ( P = 0.001). Cutoff value for PWTT%Δ3 was −2.5% (sensitivity: 86%, specificity: 90%). The gray zone for PWTT%Δ3 was identified as between −2.9% to −1.9% for which fluid responsiveness could not be predicted reliably in 6 out of 24 fluid challenges. Conclusions: In mechanically ventilated anesthetized dogs given a mini‐fluid challenge of 3 mL/kg of colloid, PWTT%Δ could predict fluid responsiveness although the gray zone should be considered.